PENGARUH ECONOMIC VALUE ADDED DAN MARKET VALUE ADDED TERHADAP RETURN SAHAM PADA PERUSAHAAN LQ 45 YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2018-2020 - Edi Sudiarto; Lailatul Badriyah; Dwi Danesty Deccasari (Sekolah Tinggi Ilmu Ekonomi Nasional (STIENAS) Banjarmasin, 2024)
This study aims to analyze the influence of Economic Value Added (EVA) and Market Value Added (MVA) on Stock Returns in LQ-45 companies listed on the Indonesia Stock Exchange (IDX) during the 2018–2020 period. The research employs a quantitative approach using multiple linear regression methods to examine the relationship between corporate financial performance and stock returns, particularly amid the impact of the COVID-19 pandemic on the capital market. The findings indicate that EVA has a negative and insignificant effect on stock returns, suggesting that economic value-added performance does not always reflect investment decisions in the stock market. In contrast, MVA has a positive and significant effect on stock returns, highlighting that higher market value positively influences investor confidence. Simultaneously, EVA and MVA were found to have an impact on stock returns with varying levels of significance. This study updates previous research by focusing on the COVID-19 pandemic period, which affected the global economy and capital market activities. The results of this research are expected to serve as a reference for investors and corporate management in optimizing financial strategies and enhancing investment attractiveness in the capital market.